1993
DOI: 10.1093/rheumatology/32.11.949
|View full text |Cite
|
Sign up to set email alerts
|

A New Biochemical Marker for Joint Injury. Analysis of Ykl-40 in Serum and Synovial Fluid

Abstract: We report the development of the first radioimmunoassay for YKL-40, a M(r) = 40 kDa protein which is secreted at high levels by human synovial cells and articular cartilage chondrocytes, and by the human osteosarcoma cell line MG63. This assay uses YKL-40 purified from the conditioned medium of MG63 cells as standard and tracer, and as antigen for immunizing rabbits. With this assay we have discovered high levels of YKL-40 antigen in serum and SF. The molecular weight of serum and SF YKL-40 is identical to pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
103
0
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(109 citation statements)
references
References 0 publications
5
103
0
1
Order By: Relevance
“…The presence of HC gp-39 in the inflamed joints of RA patients had already been demonstrated in previous investigations (13,34) and was confirmed in the present study, in which we observed high levels of HC gp-39 in the SF of all RA patients tested (10-15 fold higher than published serum levels [11][12][13]). In addition, we demonstrated the presence of MIA in both SF (ϳ3-fold higher than in serum [data not shown]) and in ST of RA patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The presence of HC gp-39 in the inflamed joints of RA patients had already been demonstrated in previous investigations (13,34) and was confirmed in the present study, in which we observed high levels of HC gp-39 in the SF of all RA patients tested (10-15 fold higher than published serum levels [11][12][13]). In addition, we demonstrated the presence of MIA in both SF (ϳ3-fold higher than in serum [data not shown]) and in ST of RA patients.…”
Section: Discussionsupporting
confidence: 92%
“…Although the physiologic function of HC gp-39 is still unknown, its expression is specifically induced under pathologic conditions such as RA (8,(11)(12)(13). In RA patients, HC gp-39 is expressed not only by chondrocytes, but also by mature CD16-positive macrophages in the synovium (14) and by peripheral blood-derived macrophages during their differentiation from monocytes (15)(16)(17)(18).…”
mentioning
confidence: 99%
“…Fraction 79 gave a band 2 at 40 kDa upon SDS-PAGE ( Fig. 1, inset) and proved to be YKL-40 by the criteria of N-terminal protein sequencing (YKLVXYYTSW-) and by radioimmunoassay (9). The next most abundant protein component in chondrocyte-conditioned medium emerges in an asymmetric peak centered at fraction 70.…”
Section: Resultsmentioning
confidence: 96%
“…YKL-40 was subsequently discovered as a heparin-binding protein in the conditioned medium of human synoviocytes (8), chondrocytes (4,9), and the MG-63 osteosarcoma cell line (10). YKL-40 has also been discovered as a heparin-binding protein expressed by porcine vascular smooth muscle cells undergoing a differentiation transition (11) and as a protein expressed selectively by murine mammary tumors initiated by neu/ras oncogenes (12).…”
mentioning
confidence: 99%
“…In contrast to chitotriosidase, a related active chitinase that is also expressed during late stages of macrophage differentiation (19), HC-gp39 lacks hydrolytic activity, probably because of a single amino acid substitution in the catalytic center region and acts as a chitin-specific lectin (20). In vivo, HC-gp39 levels are increased in serum, synovial fluid, and cartilage of rheumatoid arthritis patients (18,21), in various inflammatory disorders (22), in the liver of patients with alcoholic cirrhosis (23), in serum of patients with recurrent breast cancer (24) and colorectal cancer (25), and in macrophages in the atherosclerotic plaque (26). The described expression pattern suggests a putative role in inflammation, tissue remodeling, and tumor metastasis.…”
mentioning
confidence: 99%